The Influence of Brand Image, Product Quality and Service Quality on Customer Loyalty at Gudeg Lumintu Restaurant in Jember Regency - Ratih Puspitorini Yekti Ambarkahi; Pascawati Savitri Universitasari; Raden Roro Lia Chairina; Ponti Primastuti Aulia Nugraheni; Candra Herdiana Indah Tiara Ayuni (Journal of Business Management, 2025)
This study aims to analyze (1) the effect of brand image, product quality and service quality on customer loyalty at Gudeg Lumintu Restaurant in Jember Regency simultaneously or partially, (2) variables that have a dominant influence on customer loyalty at Gudeg Lumintu Restaurant. The data is taken directly from the respondents using a survey method through a questionnaire. The sampling technique used is incidental sampling with a sample of 40 respondents. The data an alysis technique used is multiple linear regression analysis, coefficient of determination analysis, F test and t test. The results of data analysis using SPSS 23 software show that (1) simultaneously, brand image variables (X1), product quality (X2) and service quality (X3) have a significant effect on customer loyalty (Y), (2) partially, image variables brand (X1) and product quality variable (X2) have a significant effect on customer loyalty (Y), while the service quality variable (X3) has no significant effect on customer loyalty (Y), (3) the variable that has a dominant influence on customer loyalty (Y ) is product quality (X2).